Industry for growth into the new millenium (United Nations Industrial Development Organization, 2000)
"This publication is intended to serve as a UNIDO contribution to the ongoing debate on the role of industrialization in socio-economic development in a globalizing world. This was the core issue of discussion in the Forum on Sustainable Industrial Development held in Vienna on 29 November-1 December 1999"